Capture d'innovation : étude de cas d'une néo-banque à mission sociale et défis pour les pays en développement Recapturing Innovation: A case study of Neobanking with a social mission and the challenges of its business model for developing countries. Issue 1 (2021) - Ashta, Arvind; Assadi, Djamchid; Duran, Nathalie
No abstract available